DOI: 10.32469/10355/44664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aflatoxin B₁ (AFB₁) on hepatic gene expression in pigs and turkeys

Abstract: My special thanks to my wife and best friend Marina S. Murarolli who gave me all the support and love during happy and hard times, always been by my side, helping me to make decisions. I also would like to thank my parents, Airton and Neide, for all the love and always supporting all my decisions. My brother, Vinicius, and my sister, Flaveli, for the love and friendship. My parents-in-law, Vera and Tomas, and my sister-inlaw, Marcela, always helping and advising us with their experience.Thanks to all my Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 112 publications
(146 reference statements)
2
3
0
Order By: Relevance
“…Genes involved in carcinogenesis were also significantly affected by AFB1, as demonstrated by the KEGG enrichment and PPI network analysis. For instance, the pathway “ECM-receptor interaction” was enriched, which confirms what was previously reported in LMH cell line and turkey liver [ 32 , 42 ]. The extracellular matrix (ECM) consists of several macromolecules and mineral which are essential in maintaining cell architecture and functions; ECM proteins play a central role in this rearrangement by regulating complex cellular processes [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Genes involved in carcinogenesis were also significantly affected by AFB1, as demonstrated by the KEGG enrichment and PPI network analysis. For instance, the pathway “ECM-receptor interaction” was enriched, which confirms what was previously reported in LMH cell line and turkey liver [ 32 , 42 ]. The extracellular matrix (ECM) consists of several macromolecules and mineral which are essential in maintaining cell architecture and functions; ECM proteins play a central role in this rearrangement by regulating complex cellular processes [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the death receptor genes TNFRSF10A and TNFRSF10B resulted in being upregulated in a dose-dependent way, following the exposure to AFB1. The upregulation of death receptor as a consequence of AFB1 exposure was previously reported also in pigs exposed to AFB1 in feed [42]. Moreover, our experiment highlighted an increase of expression of pro-apoptotic genes like GADD45A and CIDEB.…”
Section: Afb1 Effects On Bfh12 Cell Transcriptomesupporting
confidence: 84%
See 1 more Smart Citation
“…Previous microarray studies have shown that changes in gene expression in chicken livers after exposure to AFB1 diet are associated with energy production and fatty acid metabolism, growth and development, antioxidant protection, coagulation and immune protection, apoptosis and cell proliferation [10,11]. Functional analysis of the turkey hepatic transcription challenged with AFB1 diet showed transcripts dis-regulated by toxicity and affecting pathways of lipid regulation, cell cycle, cancer, and apoptosis [2,[12][13][14]. Nowadays, the research on transcription level is not limited to the change in mRNA expression profile, but from RNA-encoding protein to non-coding RNA, such as mRNA and miRNA and lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Azevedo demonstrated that pigs fed 1.0 mg AFB 1 kg −1 feed for 21 days had reduced growth performance associated with altered hepatic gene expression (specifically, cytochrome P450-2A19/CYP2A19 and glutathione S-transferase theta 1/GSTT1 [61]. Furthermore, the authors concluded that supplementation of 100 mg curcumin kg −1 to diets containing AFB 1 had a protective effect on changes in gene expression in liver of pigs.…”
Section: Effects On Pigsmentioning
confidence: 98%